Methyl chloride from the Aura Microwave Limb Sounder: First global climatology and assessment of variability in the upper troposphere and stratosphere. Issue 24 (16th December 2013) - Santee, M. L.; Livesey, N. J.; Manney, G. L.; Lambert, A.; Read, W. G.
<x xml:space="preserve">Abstract</x> [1] Methyl chloride (CH3Cl) is by far the largest natural carrier of chlorine to the stratosphere. Its importance in stratospheric ozone chemistry is expected to increase in the coming decades as emission controls alter the relative contributions from natural and anthropogenic halogen sources. The Microwave Limb Sounder (MLS) on NASA's Aura satellite provides the first daily global observations of CH3Cl. Here we quantify the quality of the MLS version 3 CH3Cl data (single‐profile precision of ±100 pptv; accuracy of 30–45%; vertical and horizontal resolution of 4–5 km and 450–600 km, respectively) and demonstrate their utility for scientific studies over the vertical range from 147 to 4.6 hPa. We exploit the unmatched scope of the 8 year MLS data set to investigate the spatial, seasonal, and interannual variations in the distribution of CH3Cl in the upper troposphere/lower stratosphere (UTLS). Like carbon monoxide, CH3Cl is a marker of pollution from biomass burning that can be lofted to the UTLS very rapidly by deep convection. The climatological seasonal cycle in CH3Cl reflects variability in regional fire activity and other surface sources as well as convection, and anomalous CH3Cl enhancements in the tropical upper troposphere are linked to specific episodes of intense burning. Methyl chloride is shown to be very useful as a tracer of large‐scale dynamical processes, such as diabatic descent inside the stratospheric winter polar vortices, quasi‐isentropic cross‐tropopause transport associated with the summer monsoon circulations, and effects related to the quasi‐biennial oscillation and the tropical "tape recorder".